Stratification of ovarian cancer borderline from high-grade serous carcinoma patients by quantitative serum NMR spectroscopy of metabolites, lipoproteins, and inflammatory markers - Bae, Gyuntae; Berezhnoy, Georgy; Koch, André; Cannet, Claire; Schäfer, Hartmut; Kommoss, Stefan; Brucker, Sara; Beziere, Nicolas; Trautwein, Christoph (Frontiers in Molecular Biosciences, 2023)
Background: Traditional diagnosis of ovarian cancer is based on histology or clinical stage classification which however provides no information upon tumor metabolism and inflammation. This project was an exploratory approach to profile metabolites, lipoproteins and inflammation parameters (glycoprotein A and glycoprotein B) of borderline ovarian tumor (BOT) and high-grade serous cancer (HGSOC) for identifying useful serum markers to stratify ovarian cancer patients. Methods: This project included 201 serum samples (50 BOT, 151 HGSOC) which were phenotyped by 1H-NMR based metabolomics with in-vitro diagnostics research (IVDr) standard operating procedures generating quantitative data on 38 metabolites, 112 lipoprotein parameters and 5 inflammation markers. Uni- and multivariate statistics were applied to identify NMR-based alterations. Moreover, biomarker analysis was carried out with all NMR parameters and CA-125. Results: Ketone bodies, glutamate, 2-hydroxybutyrate, glucose, glycerol and phenylalanine levels were significantly higher in HGSOC, while alanine and histidine were decreased. Inflammatory markers glycoprotein A and B (GlycA and GlycB) increased significantly over the clinical stages and were higher in HGSOC, alongside significant changes in lipoproteins. Lipoprotein subfractions of VLDLs, IDLs and LDLs increased in HGSOC and over the clinical stages, while total plasma apolipoprotein A1 and A2, and subfraction of HDLs were decreased. Additionally, LDL-triglycerides significantly increased in advanced ovarian cancer. In biomarker analysis, glycoprotein parameters performed identical to CA-125. Moreover, CA-125/GlycA, CA-125/GlycB and CA-125/Glycs are potential biomarkers for extended diagnosis of epithelial ovarian cancer (EOC). Lastly, the quantitative inflammatory parameters clearly displayed unique patterns of metabolites, lipoproteins and CA-125 in BOT and HGSOC with clinical stages I-IV. Conclusion: 1H-NMR IVDr assays could detect and identify altered metabolites and lipoproteins relevant to EOC development and progression and show that inflammation (based on glycoproteins) increased along with malignancy. As inflammation is a hallmark of cancer, glycoproteins thereof are promising future serum biomarkers for diagnosis, prognosis and treatment response of EOC. This was supported by identification of 3 different inflammatory serum classes which characterize specific alternations in metabolites, lipoproteins and CA-125, implicating that future diagnosis could be refined not only by diagnosed histology and/or clinical stages but also glycoprotein classes.